PÊNDULO ANCORADO EM MINI-IMPLANTES: AVALIAÇÃO DENTÁRIA E ESQUELÉTICA - Barros, Roger Teixeira Gazzinelli de (2009)
The pendulum appliance is efficient in correcting Class II malocclusions with upper dentoalveolar impairment. However, the loss in anchorage characterized by the mesial movement of maxillary pre-molars and by facial flaring and protrusion of maxillary incisors, represents a serious side effect of this appliance. The objective of this study was to evaluate the possible dental and skeletal alterations, both sagittal and vertical, resulting from the use of a modified Pendulum appliance anchored on mini-implants. Ten individuals were treated in this study; lateral radiographs were taken at the beginning of the study and immediately after removal of the Pendulum. In each individual, two mini-implants were installed on the palate, and received immediate charge by means of the activation of the modified Pendulum, supported on the temporary anchorage devices. None of the evaluated teeth displayed statistically significant vertical alterations; the same was true for vertical and sagittal skeletal alterations, as well as for overbite and overjet. As for statistically significant alterations, the first maxillary molar moved distally by approximately 5.6mm in 6.2 months, with average distal inclination of 7.10°. The second maxillary pre-molars moved distally by an average of 2.77mm, with inclination of 5.55°; the second maxillary molars presented an average distal movement of 4.6mm with inclination of 13.70°, values which were also considered statistically significant. The maxillary molar distalization system, consisting of the modified Pendulum appliance anchored on mini-implants, proved to be efficient in correcting Class II malocclusion, without causing the loss of anchorage effects.(AU)